Commentary on the Old Testament ; v. 3 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James; Harper, Andrew; Taylor, Sophia (Grand Rapids, MI Eerdmans)
Contents : v. 3 : I and II Kings, I and II Chronicles, Ezra, Nehemiah, Esther. Includes bibliographical references.
Reprinted 1975.
Keywords: Bible. O.T. -- commentaries